Analysis of the interaction between N-acetylneuraminic acid and disaccharides on silica surface - L. M. Ushakova; E. M. Demianenko; M. I. Terets; V. V. Lobanov; M. T. Kartel (Хімія, фізика та технологія поверхні, 2020)
Nanocomposites based on biomolecules and highly dispersed silica are quite promising for use in many fields of biotechnology. There are many methods of obtaining such materials, in particular, adsorption from liquid or gas phases. Saccharides and their derivatives are present in the human body, they are involved in metabolic process, thus it is reasonable to use them while working with biomolecules. The work considers such disaccharides as sucrose, lactose and N-acetylneuraminic acid (NANA). Being a part of glycoproteins and glycolipids, NANA is also considered to be a carbohydrate. The main objective of the study was to study the ways of interaction of NANA on the disaccharide-modified silica surface. The methods of quantum chemistry have been used to find the probable structures of three-component adsorbtion complexes at molecular level and to clarify the mutual influence of these compounds in adsorbtion process. An analysis of the results of quantum chemical calculations shows that the adsorption of an anion of N-acetylneuraminic acid on silica surface is less likely than in its molecular form. Molecules of N-acetylneuraminic acid, disaccharides and silica form intermolecular complexes due to intermolecular hydrogen bonds between polar functional (mainly –OH) groups of the analytes. The sucrose dimer is 85.4 kJ/mol stronger than the lactose one. The sucrose molecule also forms a 38.1 kJ/mol stronger intermolecular complex with the N-acetylneuraminic acid molecule compared to a similar complex where lactose is used as a disaccharide. The highest energy (245.2 kJ/mol) is released when a silica cluster interacts with the intermolecular complex of N-acetylneuraminic acid and sucrose provided silica and the sucrose molecule are in a direct contact with each other. Therefore, as studies have shown, the adsorption of N-acetylneuraminic acid is possible if silica surface is pre-modified with disaccharides. The results of quantum chemical modeling confirm the obtained experimental data.